Serum from Hypertensive Patients Induces Cancer-Supporting Phenotype of Vascular Endothelium In Vitro - Paweł Uruski; Justyna Mikuła-Pietrasik; Andrzej Tykarski; Krzysztof Książek (Biomolecules)
Background/Objectives: Large-scale epidemiological studies have established a bidirectional association between hypertension and cancer. However, the underlying mechanisms explaining this connection remain unclear. In our study, we investigated whether serum from patients with hypertension (HT) could enhance the aggressiveness of cancer cells in vitro through alterations in endothelial cell phenotype. Methods: Experiments were performed using EAhy926 endothelial cells and ovarian (SKOV-3), colorectal (SW480), pancreatic (PSN-1), breast (MCF-7), and lung (A549) cancer cell lines. Results: This study showed that conditioned medium (CM) produced by EAhy926 cells, when exposed to serum from patients with untreated hypertension (HT-CM), promotes the proliferation, migration, and invasion of every cancer cell line tested. In addition, endothelial cells subjected to HT serum promote the adhesion of all cancer cell types except PSN-1. An intensified transendothelial invasion of cancer cells was accompanied by decreased expression of junctional proteins (connexin 43, E-cadherin, occluding, desmoglein) in HT serum-treated endothelial cells. Quantitative analysis of the secretome of endothelial cells subjected to HT serum showed that they secrete increased amounts of CCL2, CXCL1, CXCL8, bFGF, HGF, IL-6, PAI-1, and TGF-β1. Moreover, cancer cells exposed to HT-CM display increased mRNA expression for several pro-cancerogenic agents, including CXCL8, tPA, and VEGF. Conclusions: Our report shows that hypertension may potentiate cancer cell aggressiveness by modulating endothelial cell phenotype. Further tests with antihypertensive drugs are required to assess whether effective treatment of hypertension can mitigate its cancer-promoting potential.